De novo variants in PAK1 lead to intellectual disability with macrocephaly and seizures - Horn, Susanne; Au, Margaret; Basel-Salmon, Lina; Bayrak-Toydemir, Pinar; Chapin, Alexander; Cohen, Lior; Elting, Mariet W.; Graham, John M.; Gonzaga-Jauregui, Claudia; Konen, Osnat; Holzer, Max; Lemke, Johannes; et al. (Brain, 2019)
Using trio exome sequencing, we identified de novo heterozygous missense variants in PAK1 in four unrelated individuals with intellectual disability, macrocephaly and seizures. PAK1 encodes the p21-activated kinase, a major driver of neuronal development in humans and other organisms. In normal neurons, PAK1 dimers reside in a trans-inhibited conformation, where each autoinhibitory domain covers the kinase domain of the other monomer. Upon GTPase binding via CDC42 or RAC1, the PAK1 dimers dissociate and become activated. All identified variants are located within or close to the autoinhibitory switch domain that is necessary for trans-inhibition of resting PAK1 dimers. Protein modelling supports a model of reduced ability of regular autoinhibition, suggesting a gain of function mechanism for the identified missense variants. Alleviated dissociation into monomers, autophosphorylation and activation of PAK1 influences the actin dynamics of neurite outgrowth. Based on our clinical and genetic data, as well as the role of PAK1 in brain development, we suggest that gain of function pathogenic de novo missense variants in PAK1 lead to moderate-to-severe intellectual disability, macrocephaly caused by the presence of megalencephaly and ventriculomegaly, (febrile) seizures and autism-like behaviour.
CRIS-Team Scopus Importer:2019-11-08
Keywords: de novo; exome sequencing; intellectual disability; macrocephaly; seizures